Association between IGF2 and CYP21 gene polymorphisms and characteristics of economic interest in Nellore cattle - da Silva, A. Martins; Rios, A. F. L.; Ramos, E. S.; Lobo, R. B.; Oliveira, Henrique Nunes de [UNESP]; de Freitas, M. A. R. (Funpec-editora, 2011)
We analyzed two single nucleotide polymorphisms (SNPs) of the IGF2 and CYP21 genes in Nellore cattle participating in the Brazilian Animal Breeding Program. The SNPs were found in exon 6 of the IGF2 (insulin-like growth factor 2) gene (RFLP/MboII) as well as in the promoter region of the CYP21 (steroid 21-hydroxylase) gene (RFLP/HpaII) of these animals. The TC heterozygotes were significantly more frequent than CC and TT homozygotes in the RFLP/MboII polymorphism. The T allele was significantly more frequent than the C allele in RFLP/HpaII polymorphism. This population was found to be in Hardy-Weinberg equilibrium for these SNPs. Association of these polymorphisms with expected progeny differences of reproductive and productive traits was investigated, but proved to be significant only for DP550 (expected progeny differenced for weight at 365 days - IGF2 - RFLP/MboII) and DP450 (expected progeny differenced for weight at 450 days - CYP21 - RFLP/HpaII). This is the first study on the occurrence of these two polymorphisms in this Zebu breed of cattle. A total of 147 Nellore animals participating in the Breeding Program of the Nellore Breed (PMGRN) under the management of the National Association of Breeders and Researchers (ANCP) in the city of Ribeirao Preto were analyzed.
Keywords: Genotype-phenotype association; SNPs; IGF2; CYP21; Cattle